SISTEM PENDUKUNG KEPUTUSAN PELANGGARAN TATA TERTIB SANTRI MENGGUNAKAN METODE SMART - Darmawan, Ricky; Andriani, Anita; Fatkhur Rizal, Muhammad; Widoyoningrum, Sri (Fakultas Teknologi Informasi, 2024)
Santri Pondok Pesantren Tebuireng 4 who violate the rules will get punishment to improve behavior and provide a deterrent effect, but the data collection of sanctions is still manual so that often repeated violations are not recorded. This research aims to design a system of decision assistance based on the SMART method to record the history of violations and determine the appropriate type of sanction automatically. This descriptive research with a quantitative approach was conducted at Pondok Pesantren Tebuireng 4, Riau, for four months. Data were collected through interviews and documentation, then used to design a system with the SMART method, which was implemented using UML for visualization and documentation of system design through diagrams such as flowcharts, use case diagrams, and activity diagrams. System testing at Pondok Pesantren Tebuireng 4 using Black Box Testing showed satisfactory results on various scenarios, such as the appearance of the login page, dynamic website functionality, report print page, and final score results. Testing was conducted with the pesantren Security Team, and the results confirmed that the SMART-based system can generate automated reports that facilitate efficient monitoring and enforcement of santri discipline. With this system, the process of selecting actions for violations becomes faster and more accurate, and allows users to easily add, edit, and delete data. Keywords: sanctions, students, SMART, decision support system.